Banking, labor force, and regional economic growth: Evidence from Indonesia - Abd Rahman Razak; Wahyoe Soedarmono; Wahdi Salasi April Yudhi (University of Merdeka Malang, 2020)
This paper examines whether regional economic growth across Indonesian provinces can be affected by the role of banking and labor force. In general, our empirical findings show that banking development is indeed positively linked to regional economic growth, although this relationship is more pronounced for poor provinces. Moreover, this paper finds that the link between banking development and regional economic growth is conditional on the degree of labor force. Specifically, the positive impact of banking on regional economic growth only occurs when labor force is sufficiently low regardless of whether we observe poor provinces or rich provinces. Eventually, this paper highlights that increasing access to bank credit is essential to boost regional economic growth, especially for poor provinces or provinces with lower labor force.JEL Classification: O16, G21, G28 How to Cite:Razak, A. R., Soedarmono, W., Yudhi, W. S. A. (2020). Banking, labor force,and regional economic growth: Evidence from Indonesia. Jurnal Keuangan dan Perbankan, 24(2), 156-163.DOI: https://doi.org/10.26905/jkdp.v24i2.3533